Vector [large type] - Abel, James (Thorndike Press, a part of Gale, a Cengage Company, 2017)
The Amazon rain forest spawns a new terror that will bring the world to its knees in this new Joe Rush bio-thriller.... Joe Rush is at an Amazon gold rush to study new forms of malaria when his best friend and partner, Eddie Nakamura, disappears. Learning that many of the sick miners have also vanished, Rush begins a search for Eddie that takes him into the heart of darkness--where he must battle for his life, and where he discovers a secret that may change the world....Thousands of miles away, floods of sick people are starting to appear in U.S. hospitals. When the White House admits that it has received terrorist threats, cities across the Northeast begin to shut down. Rush and his team must journey from one of the most remote spots on Earth to one of the busiest, as the clock ticks toward a kind of annihilation not thought possible. They have even less time than they think to solve the mystery, for the danger--as bad as it is--is about to get even worse ...